A Comparative Study of Christian Palliative Care and Chinese Soul-Summoning Rituals: Exploring Doctrinal Dialogues on the Concepts of Soul, Spirit, and Anima - FAN Junming, (Journal of Research for Christianity in China (JRCC), 2025)
Christianity's medical endeavors in modern China constituted a vital component of its missionary work. Western medicine played a significant role in the spread of Christianity in modern China, both directly and indirectly, and became a powerful tool for Christianity to counter the traditions and customs of different nations and ethnic groups. However, within the context of traditional Chinese culture and customs, Christianity also faced inherent limitations that prevented the comprehensive dissemination of Western medical practices.